Administrative Empowerment and its administrative creativity among the staff of the Youth and Sports Directorates - بن رجم ادريس (sports creativity, 2025)
In its general form, this study aims to find out whether there is a correlation between administrative empowerment and administrative creativity among a sample of employees of the directorates of youth and sports in the states of M’sila, Bordj Bou Arreridj, Biskra, Sétif, where the researcher used the descriptive approach and questionnaire as a tool for collecting information and data, and the study sample was chosen In a comprehensive inventory method, that is, the questionnaire was distributed to all employees, and 69 valid questionnaires were retrieved for statistical treatment. There is a direct correlation between teamwork and administrative creativity among the employees of the Directorates of Youth and Sports